Tyrosine kinase as therapeutic target of neurodegenerative disorders - Dipanjan Karati; Dileep Kumar (Brain Disorders)
Classes of hereditary and sporadic illnesses known as neurodegenerative diseases are linked to gradual nervous system malfunction and neuronal death. Protein kinases are an increasingly popular class of pharmacological targets for disorders affecting peripheral tissues; nevertheless, developing kinase-targeted therapies for diseases affecting the central nervous system (CNS) is still difficult, mostly because of problems related to CNS drug discovery. A class of membrane-bound receptors known as receptor tyrosine kinases (RTKs) consists of an intracellular catalytic domain, a transmembrane domain, and an extracellular ligand-binding domain. RTKs are essential for many diverse biological functions, such as motility, growth, differentiation, and metabolism. The deregulation of RTK activity aids the development of several neurodegenerative diseases. The research found that in neurological diseases, changes were made to the vascular endothelial growth factor-B TAM receptors, tropomyosin receptor kinase, and epidermal growth factor receptor 1. Furthermore, it is shown that two important routes for neurite expansion and neuronal survival triggered by RTKs are the Wnt/catenin and PI3K/Akt/GSK-3β signaling pathways. PTKs, such as non-receptor tyrosine kinases, are also important for neuronal function and the development of neurodegeneration. When aberrantly produced or activated, non-receptor tyrosine kinase (Abelson kinase) c-Abl seems to have a role in both the normal development of brain tissue and the emergence of neurodegenerative diseases. The function of both RTKs and PTKs in neurodegenerative illnesses is described in this study, with special attention to their signaling pathways and prospects for treatment.